Frequency of Polycystic Ovary Syndrome PCOS and Various Phenotypes of PCOS in a Tertiary Care Hospital - Poonam Goswami, Fouzia Perveen, Aneela Habib, Shazia Jabbar, Sadia Detho, Sarah Kazi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The commonest criteria used for diagnosis of Polycystic ovary syndrome (PCOS) are the “Rotherdam criteria” which includes any two among 1:Oligo/anovulation(O), 2:clinical and/or biochemical hyperandrogenemia (H), and 3:polycystic ovaries on ultrasound (P). Aim of the study was to determine the frequency of PCOS diagnosed on clinical findings and the frequency of phenotypes of PCOS in tertiary care hospital. Study Setting: This Cross sectional study was conducted in the Department of Gynaecology & Obstetrics, Unit 3, Civil hospital, Karachi from January, 2018 to July, 2018. Material and Methods: Total 292 patients of age 18-45 years were included. A pelvic ultrasound for status and morphology of ovary was done. After receiving laboratory and ultrasonography results diagnosis for PCOS and phenotypes was made on the basis of different combination of chronic anovulation (O), hyperandrogenism (H) and polycystic ovaries(P). Descriptive statistics were calculated. The stratification was done using chi-square test. P value ≤0.05 was considered as significant. Results: Mean age of patients was 31.37±5.72 years. 67.3% were multiparous. Mean irregular period days and number of follicles were 152.05±29.11 days and 12.66±2.46 while mean OV and mean testosterone was 11.20±6.86 cm3 and 4.36±1.51 Nmol/L. 74.3% females were found with PCOS. Among them Oligo-ovulation was 75.1%, Polycystic Ovary was 83.4%, and Hyperandrogenism was 85.35%. Phenotype A was the most common type. Conclusion: Total 74.3% females were found with PCOS. Hyperandrogenism was the highest followed by Polycystic Ovary and Oligo-ovulation. While Phenotype A was found most common phenotype.